Wave-attenuation characteristics of combined-vegetation wave break forests for big rivers with large flood water level changes - Jie Ren (IWA Publishing, 2021)
For large rivers with a compound cross section, the downstream channel has a very wide water surface during the flood season. A wide water surface, high water level, and larger wind speed will cause higher waves, increasing the threat of flooding to the dike. The design of a combined-vegetation wave break forest was put forward to achieve better wave attenuation effect. The main idea of this concept is to plant different types of vegetation at different locations in front of the dike. Three single-vegetation and four combined-vegetation forest schemes were tested under seven different water depth conditions. Both physical experiments and wave numerical simulations were carried out for each scheme to study the wave attenuation effect. The results showed that the wave attenuation effect of the single-vegetation wave break forest was significantly different under different water depth conditions, and the overall effect of the combined-vegetation of wave forest was better. Combined-vegetation wave break forests combine the advantages of different types of vegetation in different water levels, which makes it more economical and reasonable to plant by rivers with large water level variation. The proposed design ideas and methods could provide theoretical support for ecological revetment engineering of large rivers and insights for practical applications.